2012
DOI: 10.5504/50yrtimb.2011.0029
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chitosan Beads for Trypsin Immobilization

Abstract: The present study deals with the potential application of chitosan macrobeads for immobilization of trypsin. Macrobeads were prepared by precipitation and their mechanical properties were improved by covalent crosslinking using glutaraldehyde. Scanning electron microscopy studies showed that the beads size varied between 2.5 mm and 3.5 mm depending on the chitosan content and molar excess of glutaraldehyde. Trypsin (EC.3.4.21.4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Egwim et al (2012) reported that lipase immobilized onto chitosan beads had improved thermal, operational and storage stabilities. In a study performed by Kamburov et al (2011) on covalent immobilization of trypsin on chitosan macrobeads, immobilization led to the increase of the enzyme heat resistance. Adriano et al (2005) indicated that the immobilization of penicillin G on chitosan activated by glutaraldehyde can increase the stability of the enzyme 4.9-fold at 50 °C and 4.5-fold at pH 10.0.…”
Section: Effect Of Temperature On Enzyme Stabilitymentioning
confidence: 99%
“…Egwim et al (2012) reported that lipase immobilized onto chitosan beads had improved thermal, operational and storage stabilities. In a study performed by Kamburov et al (2011) on covalent immobilization of trypsin on chitosan macrobeads, immobilization led to the increase of the enzyme heat resistance. Adriano et al (2005) indicated that the immobilization of penicillin G on chitosan activated by glutaraldehyde can increase the stability of the enzyme 4.9-fold at 50 °C and 4.5-fold at pH 10.0.…”
Section: Effect Of Temperature On Enzyme Stabilitymentioning
confidence: 99%
“…A quantity (2.5 g) of chitosan was dissolved in 1% acetic (100 mL) and concentrated at 75 °C until a chitosan hydrogel was formed as described by Kamburov and Lalov. 36 To form the macrobeads, the chitosan hydrogel was introduced as droplets into 30% sodium hydroxide (100 mL). The chitosan beads produced were then washed to neutrality and oven-dried overnight at 60 °C.…”
Section: Preparation Of the Chitosan Beadsmentioning
confidence: 99%
“…The presence of reactive amino groups CHS makes it a potential candidate for enzyme binding. CHS increases the free amino group concentration available for cross-linking, thus preventing the denaturation of the targeted trypsin enzyme and mediating a substantial cross-linking with retention of high enzymatic activity (Kamburov and Lalov, 2012;Li et al, 2018). For CHS, the cross-linking reaction occurs at a higher rate at pH > 6.5 when the CHS NH 2 groups are deprotonated.…”
Section: Preparation Of Trypsin Cleasmentioning
confidence: 99%
“…For CHS, the cross-linking reaction occurs at a higher rate at pH > 6.5 when the CHS NH 2 groups are deprotonated. Glutaraldehyde acts as an amino-fixing arm, forming covalent imine bonds with the amino groups, both in CHS and trypsin (Kamburov and Lalov, 2012;Sun et al, 2017).…”
Section: Preparation Of Trypsin Cleasmentioning
confidence: 99%